Hostility and physiological responses to laboratory stress in acute coronary syndrome patients() - Brydon, Lena (Pergamon Press, 2010)
OBJECTIVE: Evidence suggests that emotional stress can trigger acute coronary syndromes in patients with advanced coronary artery disease (CAD), although the mechanisms involved remain unclear. Hostility is associated with heightened reactivity to stress in healthy individuals, and with an elevated risk of adverse cardiac events in CAD patients. This study set out to test whether hostile individuals with advanced CAD were also more stress responsive. METHODS: Thirty-four men (aged 55.9±9.3 years) who had recently survived an acute coronary syndrome took part in laboratory testing. Trait hostility was assessed by the Cook Medley Hostility Scale, and cardiovascular activity, salivary cortisol, and plasma concentrations of interleukin-6 were assessed at baseline, during performance of two mental tasks, and during a 2-h recovery. RESULTS: Participants with higher hostility scores had heightened systolic and diastolic blood pressure (BP) reactivity to tasks (both P<.05), as well as a more sustained increase in systolic BP at 2 h post-task (P=.024), independent of age, BMI, smoking status, medication, and baseline BP. Hostility was also associated with elevated plasma interleukin-6 (IL-6) levels at 75 min (P=.023) and 2 h (P=.016) poststress and was negatively correlated with salivary cortisol at 75 min (P=.034). CONCLUSION: Hostile individuals with advanced cardiovascular disease may be particularly susceptible to stress-induced increases in sympathetic activity and inflammation. These mechanisms may contribute to an elevated risk of emotionally triggered cardiac events in such patients.